Knowledge of antimicrobial stewardship and the Access, Watch and Reserve (AWaRe) classification of antibiotics among frontline healthcare professionals in Akwa Ibom State, Nigeria: a cross-sectional study - Mary R. Akpan; Idongesit L. Jackson; Unyime I. Eshiet; Sediong A. Mfon; Ekpema A. Abasiattai (BMC, 2024)
Abstract Background Antimicrobial stewardship (AMS) aims to improve antibiotic use while reducing resistance and its consequences. There is a paucity of data on the availability of AMS programmes in southern Nigeria. Further, there is no data on Nigerian healthcare professionals' knowledge of the WHO 'Access, Watch and Reserve' (AWaRe) classification of antibiotics. This study sought to assess knowledge of AMS and the AWaRe classification of antibiotics among frontline healthcare professionals in Akwa Ibom State, Nigeria. Methods This was a cross-sectional survey of 417 healthcare professionals, comprising medical doctors, pharmacists and nurses, across 17 public hospitals in Akwa Ibom State, Nigeria. A paper-based self-completion questionnaire was used to collect data from the participants during working hours between September and November 2023. Statistical analysis was done using SPSS version 25.0, with p < 0.05 indicating statistical significance. Results Four hundred and seventeen out of the 500 healthcare professionals approached agreed to participate, giving an 83.4% response rate. Most of the participants were female (62.1%) and nurses (46.3%). Approximately 57% of participants were familiar with the term antibiotic/antimicrobial stewardship, however, only 46.5% selected the correct description of AMS. Majority (53.0%) did not know if AMS programme was available in their hospitals. 79% of participants did not know about AWaRe classification of antibiotics. Among the 87 (20.9%) who knew, 28.7% correctly identified antibiotics into the AWaRe groups from a given list. Only profession significantly predicted knowledge of AMS and awareness of the AWaRe classification of antibiotics (p < 0.001). Pharmacists were more likely to define AMS correctly than medical doctors (odds ratio [OR] = 2.02, 95% confidence interval [CI] = 1.16-3.52, p = 0.012), whereas nurses were less likely to be aware of the WHO AWaRe classification of antibiotics than medical doctors (OR = 0.36, 95% CI = 0.18-0.72, p = 0.004). Conclusions There was a notable knowledge deficit in both AMS and the AWaRe classification of antibiotics among participants in this study. This highlights the need for educational interventions targeted at the different cadres of healthcare professionals on the role of AMS programmes in reducing antimicrobial resistance and its consequences.